Different methods of cutting fluid application on turning of a difficult-to-machine steel - Sanchez, L. E A [UNESP]; Palma, G. L. [UNESP]; Nalon, L. J. [UNESP]; Santos, A. E. [UNESP]; Modolo, D. L. [UNESP] (Trans Tech Publications, 2013)
Different methods of cutting fluid application are used on turning of a difficult-tomachine steel (SAE EV-8). A semi-synthetic cutting fluid was applied using a conventional method, minimum quantity of cutting fluid (MQCF), and pulverization. By the minimum quantity method was also applied a lubricant of vegetable oil (MQL). Thereafter, a cutting fluid jet under high pressure (3.0 MPa) was singly applied in the following regions: chip-tool interface; top surface of the chip; and tool-workpiece contact. Two other methods were used: an interflow between conventional application and chip-tool interface jet and, finally, three jets simultaneously applied. In order to carry out these tests, it was necessary to set up a high pressure system using a piston pump for generating a cutting fluid jet, a Venturi for fluid application (MQCF and MQL), and a nozzle for cutting fluid pulverization. The output variables analyzed included tool life, surface roughness, cutting tool temperature, cutting force, chip form, chip compression rate and machined specimen microstructure. It can be observed that the tool life increases and the cutting force decreases with the application of cutting fluid jet, mainly when it is directed to the chip-tool interface. Excluding the methods involving jet fluid, the conventional method seems to be more efficient than other methods of low pressure. © (2013) Trans Tech Publications, Switzerland.
Keywords: Cutting fluid jet; Cutting force; Minimum quantity of fluid; Pulverization; Tool life; Chip-tool interfaces; Compression rates; Conventional methods; Cutting fluid application; Cutting forces; High pressure; High pressure system; Interflow; Jet fluid; Low pressures; Output variables; Tool-workpiece contact; Top surface; Venturi; Comminution; Cutting; Grinding (machining); Industrial engineering; Machine tools; Manufacture; Surface roughness; Vegetable oils; Cutting fluids